Ownership Structure and the Survival of Listed Firms: Evidence from Korean Reverse Mergers1. (June 2015) - Han, Seung Hun; Kwon, Yonghyun
Abstract We examine the impact of ownership structure on the post‐performance of Korean firms that go public as the result of a reverse merger. Although a reverse‐merger announcement has positive cumulative abnormal returns (CARs), we find that 24.8% of reverse‐merged firms become delisted because of poor post‐performance, seemingly due to the agency problem. We also find that expected changes in management after a reverse merger positively affect the CARs of public target firms around the time of the reverse‐merger announcement. However, the post‐performance of reverse‐merged firms is relatively poor compared to firms that undertake regular initial public offerings. Further, we find that ownership concentration alleviates poor performance following a reverse merger.